PELATIHAN PENGOLAHAN ABON IKAN BERBAHAN DASAR IKAN PADANG LAMUN (KATAMBA (Lethrinus lentjan)) PADA KOPERASI PRODUSEN PESISIR NELAYAN SEJAHTERA KECAMATAN TANGGETADA, KABUPATEN KOLAKA - Ilham Antariksa Tasabaramo; Hasbiadi Hasbiadi; Arman Pariakan; Ramlah Saleh; Nenni Asriani; Masitah Masitah (Universitas Mataram, 2023)
Tanggetada District, Kolaka Regency is an area that has potential marine fisheries resources. One fishery product that has potential is seagrass fish of the Katamba type (Lethrinus lentjan). Koperasi Produsen Pesisir Nelayan Sejahtera is one of the partners involved in fish processing. The main problem for members is the low level of knowledge and skills of the members of the Partners in the processing of fishery products. One of the fish processing products carried out is the production of fish floss. Fish threading is one of the fish processing activities that can increase the added value and shelf life of fish. The objective of this community service activity is to improve the skills and knowledge of the members of the Koperasi Produsen Pesisir Nelayan Sejahtera in processing fish independently to obtain a product, namely fish floss. This community service activity will be carried out in August 2023 in Anaiwoi Village, Tanggetada District, Kolaka Regency. The activity method is carried out in several stages, including observation stage, preparation stage, training stage, mentoring and evaluation. The result of this community service activity is an increase in the skills and knowledge of partners in making Katamba fish floss. Based on the results of the interview, the partner's skill level became 90% and the knowledge level increased 100% after training. Partners are able to make fish floss according to the materials and guidebook provided. The fish floss produced in this training activity is odorless and fishy, this is because the process of making fish floss complies with the quality standards for making fish floss (SNI 7690.2013). This community service activity is able to improve the skills and knowledge of partners in making catamba fish floss.